Experience of laparoscopic cholecystectomy in patients presenting with acute cholecystitis at different duration - Pathak, Akshit; Ranjan, Alok; Kumar, Ajay; Thakur, Indra Shekhar (International Journal of Research in Medical Sciences, 2022)
Background: Acute inflammation of a gall bladder that contains stones is acute calculous cholecystitis, laparoscopic cholecystectomy is now the gold standard treatment for patients with gall stone disease. laparoscopic cholecystectomy for acute cholecystitis was initially considered technically challenging and potentially risky for the patient. Aim was to evaluate results of laparoscopic cholecystectomy in patients presenting with acute cholecystitis at different duration in a tertiary centre in eastern India. Methods: Comparative study of 71 cases of acute cholecystitis who presented at different days and were treated by laparoscopic cholecystectomy. Outcome was compared. Results: The incidence of conversion to open was 12.6%. Day of presentation 5 to 7 had the maximum 21% risk of conversion. Major intraoperative complications included 4 cases of common bile duct injury, 4 cases of vascular injury and 3 cases of bowel injury out of which vascular injury and one case of bowel injury was managed laparoscopically. 9 cases converted to open surgery. patient with DOP 1, 2 and 3 had an average hospital stays of 3 days. It was 5 for those with DOP 4 and 7 days for patients with DOP 5 to 7. Conclusions: The study supports laparoscopic cholecystectomy in acute cholecystitis specially in patients presenting within 72 hours of onset of pain. Laparoscopic cholecystectomy can be attempted in patients who present at DOP 4 and DOP 5 to7 after explaining them the risk and benefit of the procedure to the patient. Conversion to open surgery should not be stigmatized.